Academic Procrastination Reviewed From Self-Concept In Semesetr V Students Of Psychological Faculty X University In The City Of Medan: Prokrastinasi Akademik Ditinjau Dari Konsep Diri Pada Mahasiswa Semesetr V Fakultas Psikologi Universitas X Di Kota Medan - As, Irvan (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the relationship between self-concept with academic procrastination. The hypothesis of this study stated that there is a negative correlation between self-concept with academic procrastination, assuming the higher self-concept, the lower the academic procrastination and conversely the lower self-concept, the higher academic procrastination. The research subjects were 124 fifth semester students of psychology faculty at university X of medan city selected by purposive sampling method. Data were obtained from a scale to measure self-concept and academic procrastination. The calculation was performed by means of testing requirements analysis (assumption) that consists of a test for normality and linearity test for relationships. The Analysis of the data was performed by Product Moment Correlation with SPSS 17 for Windows. The results of data analysis showed that the coefficient was -0.454 and p 0.000 (p <0.05). It showed that there is a negative correlation between self-concept and academic procrastination. These results indicate that the contribution given to academic procrastination by self concept variable was 20.7 percent and the remaining 79.3 percent is influenced by other factors such as self regulated learning and self efficacy. From the results, this study showed that the hypothesis is accepted that there is a negative relationship between self-concept with academic procrastination.